TINJAUAN TEOLOGIS SIKAP GEREJA KRISTEN SUMBA TERHADAP STRATIFIKASI SOSIAL YANG ADA DI JEMAAT PAU-UMABARA - Fibry Jati Nugroho; Umbu Yanto Namu Praing (Alucio Dei, 2021)
Social stratification is a culture that is still inherent in the life of the Sumba tribe in East Nusa Tenggara. In the culture of the Sumbanese people, social stratification is very important because it will determine the level of one's position in the community. According to the people of Sumba, when the social stratification occurs, there will be a difference between maramba and ata in community life. Because when someone is in the maramba group, he will be seen as a person who has the highest position and deserves respect. But if you are in an ata group, you will be looked down upon because you have a very low position. Likewise what happened in the Pau-Umbara congregation, they still practice social stratification and they believe that with social stratification, everyone will respect each other, respect each other. Through a qualitative approach using descriptive methods, this research examines the attitude of the Sumba Christian Church towards the existing social stratification in the Pau-Umabara congregation. It is found that the Church provides a new understanding of stratification in the congregation.